New insights in the selection and management of cancer patients applicants for ovarian tissue cryopreservation. (1st November 2016) - Paradisi, Roberto; Macciocca, Maria; Vicenti, Rossella; Rossi, Stefania; Morselli-Labate, Antonio M.; Mastroroberto, Marianna; Seracchioli, Renato; Fabbri, Raffaella
Abstract: Ovarian tissue cryopreservation (OTC), representing a promising strategy to preserve ovarian function in cancer patients, is recommended to women younger than 35 years. This study aimed to identify endocrine and biometric parameters as additional selection criteria for OTC. One hundred and ninety-one cancer patients before chemoradiotherapy and OTC and 43 controls were investigated. Mean ± SD, median, quartiles, 5th and 95th centiles and correlations of FSH, LH, estradiol, inhibin-B, anti-Mullerian hormone (AMH), ovarian volume and antral follicle count (AFC) were assessed. Most ovarian reserve parameters presented typical variations of ovulatory menstrual cycle, except AMH and AFC showing minimal fluctuations across the menstrual cycle. The 5th centiles of AMH (0.31and 0.4 ng/mL in controls and cancer patients, respectively) and AFC (five follicular structures in both groups) could be conjectured as minimum thresholds to include patients aged <35 years in OTC; below this threshold patients of any age should be excluded from OTC. Conversely, patients with AMH and AFC above the 25th centiles (1.2–1.6 ng/mL and 9–10 follicular structures in controls and cancer patients, respectively) might be inserted in OTC regardless of age. Baseline assessment of AMH and AFC might be considered as selection criteria, in addition to chronological age, to take decision of OTC in cancer patients.